Schwannoma of the tongue: a case report - İbrahim Çukurova; Doğan Özkul; Erhan Demirhan; İlker Burak Arslan; Ümit Bayol (Turkish Archives of Otorhinolaryngology, 2009)

(untitled)
Schwannoma is a benign slow-growing tumor which originates from peripheral, autonomic or cranial nerve sheaths. Schwannomas most often occur in the head and neck (40- 50%) or on the flexor surfaces of the extremities. It mostly originates from vagus and also originates from the other nerves of parapharyngeal region. Malignant transformation is very rare. Oral cavity remains a rare site. Because of resistance to radiotheraphy, surgical excision is necessary for optimal treatment. We purpose to present a case of Schwannoma of the tongue.